(untitled) (Marketing Journal, 2025)
This article is dedicated to the statistical analysis of the unemployment rate in the Republic of Uzbekistan. It examines the unemployment rate and its causes, as well as factors influencing household incomes and economic growth. As a result, practical recommendations for reducing unemployment are provided based on international experience and the specific conditions of Uzbekistan.